Shedding Light on Trust - Gill, Lesley; Ramsey, Phil (APMBA (Asia Pacific Management and Business Application), 2012)
New Zealand Human Resource Development practitioners interviewed in earlier research indicates that building trust is necessary if training efforts in the area of Emotional Intelligence are to be successful. Yet, trust is often not defined clearly by those working in the field of HRD.  To establish a definition of trust that provides HRD practitioners with direction in the design of training programs, a large group conversation utilizing the World Caf process was undertaken, after which EI training practitioners wrote reflections on the nature of trust.  Experienced EI Trainers tended to define trust in terms of the outcome produced in training, which was the readiness of participants to talk.  Defining trust in this way has the advantage of involving a low level of inference.  Trainers also identified actions within their control that could stimulate greater readiness amongst training participants about their experiences to trainers and other learners. The aim of the article is to provide a practice-based definition of trust that can inform HRD practitioners working in the field of Emotional Intelligence.